Comparison of microwave irradiation and conventional thermal heating on volatile profiles and degree of oxidation in corn oil. (26th November 2022) - Kim, SeHyuk; Choi, Hyuk; Lee, YoonHee; Lee, JaeHwan
Summary: Volatile profiles and degree of oxidation in corn oils after microwave treatment for 50 min were compared to oils with conventional heating at 180°C for 4 h. Oil microwaved for 10 and 50 min showed a similar degree of oxidation compared to the oil heated at 180°C for 1 and 3 h, respectively, based on the primary and secondary oxidation products. However, the total volatile contents of 50 min‐microwaved oil were significantly lower than that of corn oil heated for 1 h at 180°C ( P < 0.05). Microwave treatment accelerated the rates of lipid oxidation by 4.6 times compared to 180°C thermal oxidation. Relatively short treatment with microwave irradiation may not provide sufficient time to generate volatiles from oil. Microwaved corn oil for 50 min had higher contents of hexanal and t ‐2‐heptenal and lower contents of 2, 4‐decadienal and nonanal than the oils heated at 180°C for 3 h. Reactive oxygen species may be involved in volatile formation in microwave‐irradiated oils. Abstract : Corn oils were treated by microwave irradiation and a 180°C oven, and volatile profiles and degree of oxidation were compared. Microwave irradiation accelerated rates of oxidation by 4.6 times compared to oven treatment based on primary and secondary oxidation. Total volatile contents of microwaved oil were lower than those of oven‐treated oil at similar degree of oxidation. Microwaved oil had higher hexanal and t ‐2‐heptenal and lower 2, 4‐decadienal and nonanal than heated oils. Reactive oxygen species may be involved in the volatile formation in microwave‐irradiated oils.